2011
DOI: 10.4172/2161-0509.1000102
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Investigations on Medicinal Herbs Possessing Anti-Diabetic Properties

Abstract: Globally, the pervasiveness of chronic, non-communicable disease diabetes mellitus is growing by leaps and bounds. It is one of the major causes of premature morbidity and mortality worldwide. Almost 3.2 million people die of diabetes across the world every year. The worldwide prevalence of diabetes is 6.4% (corresponding to 285 million people); this varies from 10.2% in the Western Pacific to 3.8% in the African region and expected to grow up to 7.4% (439 million) of the adult population by 2030. In the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 176 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…Similarly, flavonoids, alkaloids, and saponins were found as 97, 7, and 20 mg/gm in root powder of same herb. A vast literature provides scientific evidence that plants rich in flavonoids possess potent antidiabetic, hypolipidemic, hypotensive, anti-inflammatory, and antioxidative activities [5, 38]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, flavonoids, alkaloids, and saponins were found as 97, 7, and 20 mg/gm in root powder of same herb. A vast literature provides scientific evidence that plants rich in flavonoids possess potent antidiabetic, hypolipidemic, hypotensive, anti-inflammatory, and antioxidative activities [5, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, plant-based medicines are water soluble with no side effect. It has been reported that over 80%, world population is dependent on herbal medicine for their therapeutic benefits [4], and more than 800 plant species have been mentioned in the literature with significant hypoglycemic activity [5]. However, searching for new antidiabetic drug from natural sources including herbs is still an attractive research aspect as these are cost effective substances with no side effect.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of soluble fibers from different sources such as oat , barley , guar gum , and high‐viscosity hydroxypropylmethylcellulose , into a meal has been shown in many clinical studies to reduce postprandial insulin and glucose responses. Fenugreek, a leguminous herb commonly used in Indian and Middle Eastern cuisine, has been used for decades in the treatment of diabetes . Over 30 studies in animal models and humans have reported on the antidiabetic properties of this plant's seeds .…”
Section: Overview Of Food Products and Dietary Constituents Reported mentioning
confidence: 99%
“…Medicinal plants, herbs, and their derivatives have been used for centuries in the traditional treatment of diabetes, and are being studied intensively for their mechanism of action and active principles . The consumption of various foods has also been shown in animal and human studies to have positive impacts on blood glucose regulation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, various plants have been found to possess significant antidiabetic property after their preclinical and clinical evaluation [5]. …”
Section: Introductionmentioning
confidence: 99%